Medicine and society in early modern Europe - Lindemann, Mary. (Cambridge : Cambridge University Press, 2010)
'Medicine and Society in Early Modern Europe offers students a concise introduction to health and healing in Europe from 1500 to 1800. Bringing together the best recent research in the field, Mary Lindemann examines medicine from a social and cultural perspective, rather than a narrowly scientific one. Drawing on medical anthropology, sociology and ethics as well as cultural and social history, she focuses on the experience of illness and on patients and folk healers as much as on the rise of medical science, doctors and hospitals. This second edition has been updated and revised throughout in content, style, and interpretations and new material has been added, in particular, on colonialism, exploration and women. Accessibly written and full of fascinating insights, this will be essential reading for all students of the history of medicine and will provide invaluable context for students of early modern Europe more generally'--Provided by publisher.
1. Sickness and health -- 2. Plagues and peoples -- 3. Learned medicine -- 4. Learning to heal -- 5. Hospitals and asylums -- 6. Health and society -- 7. Healing -- Conclusion.
Includes bibliographical references and index.
Keywords: Social medicine -- Europe -- History; Medicine -- Europe -- History; Medical care -- Europe -- History; Public health -- Europe -- History; History of Medicine -- Europe; History, 16th Century -- Europe; History, 17th Century -- Europe; History, 18th Century -- Europe; Public Health -- history -- Europe; Social Medicine -- history -- Europe